2008
DOI: 10.1080/01635580801966195
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Accelerates Mouse Mammary Tumor Growth in the Absence of Ovarian Hormones

Abstract: Obesity increases incidence and mortality of breast cancer in postmenopausal women. Mechanisms underlying this association are poorly understood. Suitable animal models are needed to elucidate potential mechanisms for this association. To determine the effects of obesity on mammary tumor growth, nonovariectomized and ovariectomized C57BL/6 mice of various body weights (lean, overweight, and obese) were implanted subcutaneously with mammary tumor cells from syngeneic Wnt-1 transgenic mice. In mice, the lean phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 39 publications
3
49
1
Order By: Relevance
“…These findings in two different luminal models of breast cancer are in contrast to previous reports in mouse or rat models of other mammary tumor subtypes (or with undefined subtypes) that show DIO enhances mammary tumor growth (Dogan et al 2007, Nunez et al 2008, Gu et al 2011, Dunlap et al 2012. For example, MMTV-Wnt1 mammary tumors display a molecular profile similar to many mouse and human basal-like mammary tumors, and their growth is highly responsive to changes in circulating IGF1 and is enhanced in DIO mice, and reduced in CR mice, relative to controls (Nunez et al 2008, Dunlap et al 2012). In that model, MMTV-Wnt1 tumor cells were injected into syngeneic C57BL/6 mice, which generally gain more weight and have higher IGF1 levels on the DIO diet than FVB mice, the background strain of the Met1 cells, and MMTV-Wnt1 brei used in the present experiments, as well as the MMTVneu mice used by Cleary et al (2004).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…These findings in two different luminal models of breast cancer are in contrast to previous reports in mouse or rat models of other mammary tumor subtypes (or with undefined subtypes) that show DIO enhances mammary tumor growth (Dogan et al 2007, Nunez et al 2008, Gu et al 2011, Dunlap et al 2012. For example, MMTV-Wnt1 mammary tumors display a molecular profile similar to many mouse and human basal-like mammary tumors, and their growth is highly responsive to changes in circulating IGF1 and is enhanced in DIO mice, and reduced in CR mice, relative to controls (Nunez et al 2008, Dunlap et al 2012). In that model, MMTV-Wnt1 tumor cells were injected into syngeneic C57BL/6 mice, which generally gain more weight and have higher IGF1 levels on the DIO diet than FVB mice, the background strain of the Met1 cells, and MMTV-Wnt1 brei used in the present experiments, as well as the MMTVneu mice used by Cleary et al (2004).…”
Section: Discussioncontrasting
confidence: 55%
“…Mice were individually housed with free access to water and exposed to a 12 h light:12 h darkness cycle and allowed to acclimate for 1 week before syngeneic orthotopic transplantation of Wnt1 mammary tumor brei, as previously described (Nunez et al 2008). In brief, a suspension of MMTV-Wnt1 mammary tumor cells was derived (Varticovski et al 2007) from six spontaneously developed mammary carcinomas in MMTV-Wnt1 FVB/NJ (002934; Jackson Laboratory, Bar Harbor, ME, USA, http:// www.jax.org).…”
Section: Mmtv-wnt1 Tumor Transplantation Monitoring and Sample Collmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats fed a HFD develop increased breast tumors in response to the carcinogen 7,12 dimethylbenz(a)anthracene (Carroll & Braden 1984, Braden & Carroll 1986, Rose et al 1993, Hakkak et al 2005. Furthermore, transplanted tumor xenografts demonstrate more rapid growth in rodents on HFD (Nunez et al 2008). HFD-induced obesity in rodents leads to insulin resistance, which in turn enhances tumor development.…”
Section: Role Of Sex Hormonesmentioning
confidence: 99%
“…A study at NIH concluded that obesity accelerated tumor growth in ovariectomized mice, but did not have the same effect on mice with intact ovaries, supporting the assertion that overweight status and obesity have some kind of relationship with hormonal status, which impacts breast cancer incidence and mortality. 23 A more recent study found that increased BMI was independently associated with poorer recurrence-free survival, and these outcomes were worst for younger patients with increased BMI and node-positive disease. 24 The link between healthy lifestyle choices and longevity may in the end prove to be equally as important as that between overnutrition and cancer.…”
Section: Breast Cancermentioning
confidence: 98%